The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4238/2014.december.19.11
|View full text |Cite
|
Sign up to set email alerts
|

Use of elephant grass for energy production in Campos dos Goytacazes-RJ, Brazil

Abstract: ABSTRACT. Elephant grass is a tropical forage plant widely distributed throughout Brazil. It was first exclusively used in the livestock sector as cattle feed. The grass is characterized by its high productivity and photosynthetic capacity and is considered as an alternative source of renewable energy. Here, we estimated the general combining ability of the parents and specific combining ability of the hybrids based on morpho-agronomic biomass-quality traits. The experiment was conducted in a randomized block … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
0
8
0
3
Order By: Relevance
“…This fact confirms this species diversity for biomass production. Likewise, Daher et al (2014) had observed variability among 16 hybrids concerning the same agronomic traits related to energy purposes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact confirms this species diversity for biomass production. Likewise, Daher et al (2014) had observed variability among 16 hybrids concerning the same agronomic traits related to energy purposes.…”
Section: Resultsmentioning
confidence: 99%
“…The biomass quality traits were assessed at the Laboratory of Animal Science, Darcy Ribeiro State University of North Rio de Janeiro (LZO/UENF). DMP was estimated using the percentage of dry matter and the weight of tillers from individual plants, as described by Daher et al (2014). Yet the percentage of neutral detergent fiber (%NDF) was determined as described by Mertens (2002), using a filter bag Technique (Ankom TM ).…”
Section: Methodsmentioning
confidence: 99%
“…Para a característica %LIG, na comparação das médias, os genótipos não diferiram no 1º corte, enquanto no 2º corte, foram observadas algumas diferenças e, neste caso, os híbridos H6, H8 e o genitor P6 diferiram do híbrido H10, cuja média foi de 6,24%. Daher et al (2014) ao avaliarem a capacidade de combinação em capim-elefante por meio da análise dialélica constataram que a combinação hibrida resultante ente Vruckwona x Taiwan A-146, H6 no presente estudo, apresenta alto teor de fibras e que o genótipo P6 pode ser utilizado em programas de melhoramento cujo objetivo seja a melhoria da qualidade da biomassa em capim-elefante para fins energéticos. Ao analisar o comportamento dos genótipos nos dois cortes simultaneamente, observou-se que eles apresentaram maior teor de lignina na matéria seca do 1º corte.…”
Section: Resultsunclassified
“…Some plants have shown potential to be used as sources of bioenergy, namely: elephant grass (Daher et al, 2014;Rocha et al, 2015;Salazar-Zeledón et al, 2015;Ghosh, 2016;Menezes et al, 2016), sugarcane (Szczerbowski et al, 2014;Bordonal et al, 2015), sorghum (Silva et al, 2016), and eucalyptus (Eufrade Junior et al, 2016). However, in contrast to elephant grass, which shows high photosynthetic efficiency with high biomass productivity potential, some of these cultures show low dry biomass production.…”
Section: Introductionmentioning
confidence: 96%